Argon plasma coagulation for inferior turbinate reduction - Bergler, Wolfgang; Götte, Karl; Riedel, Frank; Hörmann, Karl (Annals of otology, rhinology & laryngology, 2000)
Surgical reduction of the inferior turbinate remains a widely used therapy for nasal obstruction caused by hyperplastic turbinates. Current methods are costly and time-consuming, require nasal packing, and cause extended postoperative swelling. Argon plasma coagulation (APC) is a new, innovative technique in otorhinolaryngological surgery that is based on high-frequency electrical current. The current is transmitted through ionized argon gas (plasma) contact-free to the tissue surface and creates a coagulation and devitalization zone with limited penetration. Forty-five patients with nasal obstruction were treated under local anesthesia for reduction of the inferior turbinates with APC. Seventy-six percent of the patients reported an improvement of postoperative swelling within the first week. After 3 months, 86% reported having better nasal airflow than they had before the operation. Macroscopically, after 4 weeks the turbinate was covered by normal mucosa in 51% of the patients. Crust formation was minimal, and no bleeding occurred. Turbinate reduction with APC is an alternative technique with many advantages, and the results are comparable to those of standard techniques. Ninety-five percent of the patients were satisfied with the operation.